Dyadic Concordance in Victimization within the Family: results from a New Approach for a Nationally Representative Sample of USA Families = Concordancia diádica en la victimización intrafamiliar : resultados de una nueva aproximación en una muestra nacional representativa de familias estadounidenses - Straus, Murray A. (Revista de victimología, 2015)
This article presents empirical results on an approach to victimization research and practice intended to provide a practical way to take into account the frequent overlap of victimization and perpetration. The approach is to begin research or interventions by identifying the Dyadic Concordance Type (DCT) of the cases. For example, the DCTs for cases of partner physical violence are Female-Only victim, Male-only victim, and Both victims. They are identi ed by determining if the female partner had been attacked, if the male partner had been attacked, and then cross-classifying those two variables. For parent-child violence the three DCTs are named Parent-Only, Child-Only, and Both victims of violence by the other. The percent in each of these DCTs covering three domains of victimization: (1) Parent-child relationships (concordance in being a victim of violence by father and mother and concordance in victimized by violence between parents). (2) Problematic behaviors of partners (drunkenness and chronic aggression of partner). (3) Partner abuse (physical assault, chronic denigration, and intransigence by a marital or cohabiting partner). An important percentage of families were found in all three DCTs. However, the most frequent type was Both victims. That is, when there is victimization in a family relationships, both parties in the relationship are typically victims, rather than one being the victim and the other the perpetrator. Implication for victimization theory, research and practice are suggested.